Untersuchungen über Gallmücken (Diptera: Cecidomyiidae). IX. Contarinia molluginis (Rübsaamen 1889) Kieffer 1896 und Contarinia acrocecis n. sp. - Stelter, Helmut (Contributions to Entomology = Beiträge zur Entomologie, 1962)
A new gall on Galium mollugo L. and their producer, the gallmidge Contarinia acrocecis n. sp., are described and compared with Contarinia moiiuginis (Rübsaamen 1889) Kieffer 1896. Nomenclatural Actsacrocecis Stelter, 1962 (Contarinia), spec. n.